2017
DOI: 10.1039/c6en00415f
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-driven TiO2/Ag3PO4 heterostructures with enhanced antifungal activity against agricultural pathogenic fungi Fusarium graminearum and mechanism insight

Abstract: TiO2/Ag3PO4 heterostructures improved the separation efficiency of electron–hole pairs and enhanced the photocatalytic disinfection efficiency for F. graminearum macroconidia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…TiO 2 NPs 8-10 nm had superior antibacterial activity than TiO 2 NPs 90-100 nm and the TiO 2 NPs 8-10 nm had superior antibacterial activity on E. coli over S. aureus. The size-dependent antibacterial activity of NPs is an interesting phenomenon wherein antibacterial potential of NPs increases with decrease in the size [3,12].Recently, palladium NPs of three different sizes, viz., 2.0, 2.5 and 3.1 nm were tested on cells of E. coli and S. aureus and it was observed that NPs of size 2.0 nm showed far better antibacterial activity over NPs of sizes, 2.5 and 3.1 [13]. Apart from size dependent antibacterial activity, TiO 2 NPs also showed organism specific antibacterial property.…”
Section: Discussionmentioning
confidence: 99%
“…TiO 2 NPs 8-10 nm had superior antibacterial activity than TiO 2 NPs 90-100 nm and the TiO 2 NPs 8-10 nm had superior antibacterial activity on E. coli over S. aureus. The size-dependent antibacterial activity of NPs is an interesting phenomenon wherein antibacterial potential of NPs increases with decrease in the size [3,12].Recently, palladium NPs of three different sizes, viz., 2.0, 2.5 and 3.1 nm were tested on cells of E. coli and S. aureus and it was observed that NPs of size 2.0 nm showed far better antibacterial activity over NPs of sizes, 2.5 and 3.1 [13]. Apart from size dependent antibacterial activity, TiO 2 NPs also showed organism specific antibacterial property.…”
Section: Discussionmentioning
confidence: 99%
“…According to published studies, the sporicidal properties of nanoparticles on various phytopathogenic fungi in vitro and in vivo have been widely reported, involving metals, metal oxide nanoparticles, single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), and GO (Dong et al, 2013;Chen et al, 2016b;Liu et al, 2017). A similar work has been reported by Wani and Shah (2012) where nMgO displayed nanotoxicity on several agricultural pathogenic fungi and significant inhibition of the germination of spores of Alternaria alternata, F. oxysporum, Rhizopus stolonifer, and Mucor plumbeus.…”
Section: Figure 3 | Mycelium Colony Diameter Of Phytophthora Nicotianmentioning
confidence: 99%
“…A series of inorganic and organic nanomaterials have been developed and proven to exhibit prominent antibacterial, antifungal, and antiviral properties on phytopathogenic microbes in vitro, and some of them still exerted their toxicity effects under greenhouse and field conditions. To date, TiO 2 , CuO (Hao et al, 2017(Hao et al, , 2019Liu et al, 2017), Zn, ZnO (Xue et al, 2014;Antonoglou et al, 2018;Sun et al, 2018), carbon nanomaterials (Chen et al, 2014(Chen et al, , 2016b, Al, and Si nanoparticles (Park H.J. et al, 2006;Shenashen et al, 2017) have been reported to display toxicity toward phytopathogenic bacteria and fungi, decreasing the disease incidence.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, due to their unusual superior physicochemical properties, high surface-to-volume ratio and unique nanosize structure characteristics, several inorganic and organic metal oxide nanomaterials, and several hybrid nanomaterials, such as TiO 2 , ZnO, CuO ( Kalhapure et al, 2015 ), graphene oxide ( Chen et al, 2014 ), and Fe 3 O 4 -Ag core shell magnetic nanoparticles ( Hemeg, 2017 ), are being increasingly applied as alternative antibacterial agents in biomedical applications. Recent investigations have demonstrated that they exhibit strong antimicrobial activity toward the pathogenic bacteria Streptococcus mutans ( Liu et al, 2014 ) and Xanthomonas perforans ( Paret et al, 2013 ), fungi Fusarium graminearum ( F. graminearum ) ( Liu et al, 2017 ) and a few viruses ( Mishra et al, 2011 ). With their high pertinence to antibacterial applications, the use of nanoparticles for the prevention and control of plant diseases is a promising and valuable topic because of their increased effectiveness, durability and, particularly, their high specific surface area, which can stimulate interactions with living cells ( Kang et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%